2014
DOI: 10.1371/journal.pone.0087706
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 (PGE2) Exerts Biphasic Effects on Human Tendon Stem Cells

Abstract: Prostaglandin E2 (PGE2) has been reported to exert different effects on tissues at low and high levels. In the present study, cell culture experiments were performed to determine the potential biphasic effects of PGE2 on human tendon stem/progenitor cells (hTSCs). After treatment with PGE2, hTSC proliferation, stemness, and differentiation were analyzed. We found that high concentrations of PGE2 (>1 ng/ml) decreased cell proliferation and induced non-tenocyte differentiation. However, at lower concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
(42 reference statements)
2
23
0
1
Order By: Relevance
“…Further, hTSCs exposed to high levels of PGE 2 also expressed high levels of non-tenocyte markers PPARγ, collagen II and osteocalcin, when implanted into rats [33] and lead to non-tendinous tissue formation. Taken together, these findings suggest that factors such as aging, excessive exercise and high PGE 2 levels can induce aberrant differentiation of TSCs in otherwise healthy tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Further, hTSCs exposed to high levels of PGE 2 also expressed high levels of non-tenocyte markers PPARγ, collagen II and osteocalcin, when implanted into rats [33] and lead to non-tendinous tissue formation. Taken together, these findings suggest that factors such as aging, excessive exercise and high PGE 2 levels can induce aberrant differentiation of TSCs in otherwise healthy tendons.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that culturing TSCs along with insulin-like growth factor 1 (IGF-1) for 28 days retained multipotency in TSCs, and upregulated decorin and scleraxis expression (33). In addition, hypoxic culture conditions and low levels of PGE 2 could also enhance the stemness of TSCs in culture (34, 35). Second, the age of the donor might significantly affect the outcome of TSC treatments.…”
Section: Use Of Tscs To Treat Tendon Injuriesmentioning
confidence: 99%
“…After washing the hydrogels three times with PBS, fluorescence microscopy was performed using an Olympus IX83 microscope with a spinning disc confocal attachment. Brightfield and fluorescent‐channel images of spheres were analyzed using the ImageJ software (NIH) for the semiquantification of EdU‐positivity as described previously (Gansau & Buckley, ; Kilani et al, ; Zhang & Wang, ; Zhang, Pan, Im, Fu, & Wang, ). The fraction of EdU‐positivity was calculated as the area of the positively‐stained cells divided by the total area of the spheroid.…”
Section: Methodsmentioning
confidence: 99%
“…Brightfield and fluorescent-channel images of spheres were analyzed using the ImageJ software (NIH) for the semiquantification of EdUpositivity as described previously (Gansau & Buckley, 2018;Kilani et al, 2003;Zhang & Wang, 2014;Zhang, Pan, Im, Fu, & Wang, 2011).…”
Section: -Ethynyl-2′-deoxyuridine Assaymentioning
confidence: 99%